The mature student's study guide essential skills for those returning to education or distance learning - Dawson, Catherine (How To Books, 2006)
A study guide for those who have decided to return to education and want to bring their study skills up to scratch. Whether you are considering a full-time course, part-time studies, evening classes or distance learning such as an Open University degree, this book contains information that you need to know to succeed in your chosen course.